Pengaruh Upah Minimum, Tingkat Penidikan, Investasi, dan Akses Internet terhadap Tingkat Pengangguran Terbuka di Indonesia - Alya Viola Agusti; Idris (Media Riset Ekonomi Pembangunan (MedREP), 2026)
The open unemployment rate (TPT) remains a key indicator reflecting labor market issues in Indonesia. This study aims to analyze the impact of the minimum wage, education level, investment, and internet access on the open unemployment rate in Indonesia. A quantitative approach using panel data covering 34 provinces over the 2018–2024 period was employed. Data were obtained from Statistics Indonesia (BPS) and the Investment Coordinating Board (BKPM). Analysis was conducted using panel data regression, involving model selection, classical assumption testing, partial and simultaneous tests, and the coefficient of determination. The results indicate that the minimum wage and education level have a positive and significant effect on the open unemployment rate. Investment has a positive and significant effect on the open unemployment rate, whereas internet access has a negative but insignificant effect. Collectively, the four variables have a significant impact on the open unemployment rate in Indonesia. These findings suggest that labor policies need to be integrated with efforts to improve human resource quality, create an investment climate capable of absorbing labor, and develop more equitable digital infrastructure to support the reduction of the open unemployment rate.